Pembelajaran Matematika Realistik Berbasis Kearifan Lokal untuk Meningkatkan Kerjasama Siswa pada Materi Segi Empat - Rina Asmiati (Jurnal Didaktika Pendidikan Dasar, 2020)
This research aims to apply realistic mathematics education based on local wisdom to improve collaboration and student learning outcomes in quadrilateral material in class VIID SMP Negeri 1 Muara Tiga, Pidie Regency, which consist of 28 students. This research is a classroom action research conducted using two cycles.  The data collection of this research was collected at the end of every  cycle by using the instrument of collaboration and student learning outcomes tests. The result of this research indicates an increase in student collaboration in each cycles. preliminary data on student collaborationis  43.75% with classical completeness  53.57% then the collaboration increased to 62.5% in the first cycle with classical mastery  67.86% and collaboration increased to 75% in the second cycle with classical mastery  85.71%. So it can be concluded that realistic mathematics education based on local wisdom can increase collaboration and student learning outcomes.